Anxiolytic effect of the hydroalcoholic extract of Aeonium spathulatum "Rosa verde" in albino mice - Huancayo – 2023. - Poma Vivas , Mónica Evencia (2024)
Objective: To evaluate the anxiolytic effect of the hydroalcoholic extract of Aeonium spathulatum "rosa verde" in albino mice - Huancayo - 2023. Material and Methods: Applied research of experimental design with posttest and control group, where three experimental groups were manipulated with the hydroalcoholic extract of Aeonium spathulatum "rosa verde”, the standard group was administered with diazepam and the control group was given placebo. The anxiolytic effect was analyzed by unidirectional ANOVA followed by the Tukey test. Values with p<0.05 were considered statistically significant. Results: There are significant differences in the time of mouse permanence in the open and closed spaces, in the control group and experimental groups respectively, being the p value ANOVA equal to 0.000. According to Tukey’s analysis, the diazepam group, Aeonium spathulatum "green pink" 250mg and Aeonium spathulatum "green pink" 500mg, show significant difference p< 0.05 compared to the control group and Aeonium spathulatum "green pink" 125mg. Conclusions: The hydroalcoholic extract of Aeonium spathulatum in concentrations of 250mg has greater anxiolytic effect after diazepam.